Structure and distribution of gynaecological diseases for girls and teenage girls in the Zaporizhzhia area - N. V. Avramenko; O. V. Kabachenko; T. O. Tsaruk (Zaporozhye State Medical University, 2016)
Background. In recent years the question of gynecological diseases in women and teenage girls becomes more and more relevance. Girls of pubertal age should become mothers of new generation, but the health of adolescents continues to deteriorate. Aim. To study the structure of gynecological diseases among children and teens in the Zaporizhzhia region, to develop the main ways of improving the provision of specialized gynecological medical care in the region. Methods. The analysis of major morbidity, prevalence and patterns of gynecological diseases among girls and adolescent girls in the Zaporozhye region over the past 5 years has been done. Results. The analysis showed that the indicator of gynecological morbidity remain high and increases. Main gynecologic pathologies are: menstrual function disorders, sexual development disorders, inflammatory diseases of external and internal genitalia. Detection of pathology among girls who turned to the doctor meets in average 23-24% of cases. In girls, of the youngest age (under 10 years) inflammatory diseases of the external genitalia (vulvovaginitis, vulvitis) dominate in most cases. In teenage girls the menstrual dysfunction is prevalent. Among menstrual dysfunction the hypomenstrual syndrome is prevalent in 70% (oligomenorrhea, opsomenorrhea, amenorrhea). The Department of Health of Zaporizhzhia Regional State Administration has prepared the order of 15.02.2016r. №158 «On improvement of specialized gynecological care for children of the region", which provides specialized gynecological care to girls and teenage girls, and indications for gynecologist consultation of children and adolescent. Conclusions: In the analysis of morbidity during 5 years a significant increase in the incidence of gynecological morbidity of girls and teenage girls has revealed. Risk factors of menstrual function disorders are: thyreiod gland pathology, diabetis mellitas, bronchial asthma, congenital heart diseases, chronic infection, psychological, social factors.